Plastic strain in metals by shear banding. II. Numerical identification and verification of plastic flow law (Archives of Mechanics - Test, 2002)
The paper is devoted to the identification and verification of the constitutive description of plastic flow accounting for the hierarchy of shear banding, which is proposed in the companion paper [1]. The numerical identification was carried out with use of the experimental results obtained in channel-die test for polycrystalline copper [2]. To verify the identified model, numerical simulation of the forging process was made and the calculated values of load subjected to the punch versus its displacement were compared with pertinent experimental data given in [11].